MDG-1, a Potential Regulator of PPARα and PPARγ, Ameliorates Dyslipidemia in Mice - Xu Wang (International Journal of Molecular Sciences, 2017)
Hyperlipidemia is a serious epidemic disease caused by lipid metabolism disorder, which is harmful to human health. MDG-1, a β-d-fructan polysaccharide extracted from Ophiopogon japonicus, has been shown to improve abnormal blood lipid levels and alleviate diabetes. However, the underlying mechanism on hyperlipidemia is largely unknown. In this study, male C57BL/6 mice were randomly separated into three groups, respectively: low-fat diet (Con), high-fat diet (HFD), and high-fat diet plus 5‰ MDG-1 (HFD + MDG-1). Body weight was measured and the serum lipid levels were analyzed. Using gene microarray, various core pathways, together with levels of gene expression within hepatocytes, were analyzed. RT-PCR was used to confirm the identity of the differentially expressed genes. MDG-1 could prevent obesity in HFD-induced mice and improve abnormal serum lipids. Besides, MDG-1 could regulate hyperlipidemia symptoms, specifically, and decrease fasting blood glucose, improve glucose tolerance, and ameliorate insulin resistance. According to results from gene microarray, most of the identified pathways were involved in the digestion and absorption of fat, biosynthesis, and catabolism of fatty acids as well as the secretion and biological synthesis of bile acids. Furthermore, MDG-1 may act upon peroxisome proliferator-activated receptors (PPAR) α and γ, activating PPARα whilst inhibiting PPARγ, thus having a potent hypolipidemic effect.